(D). [tex]\%\,change=\frac{100(k-m)}{(100+m)}[/tex]
In the question,
Let us say the Price per Share, initially = 100x
and,
Earnings per Share = 100y
So,
Percent increase in Price per share = k%
Percent increase in Earning per share = m%
So,
New Price per Share = 100x + kx = (100 + k)x
and,
New Earnings per Share = 100y + my = (100 + m)y
Now,
Initial ratio of Price per Share to Earnings per share = 100x/100y = x/y
And,
Final ratio of Price per Share to Earning per share is,
[tex]\frac{(100+k)x}{(100+m)y}[/tex]
Now,
Percent increase in the ratio of Price per share to Earnings per share is,
[tex]\%\,change=\frac{\frac{(100+k)x}{(100+m)y}-\frac{x}{y}}{\frac{x}{y}}\times 100\\\%\,change=\frac{\frac{x}{y}(\frac{(100+k)-(100+m)}{(100+m)})}{\frac{x}{y}}\times 100\\\%\,change=\frac{100(k-m)}{(100+m)}[/tex]
Therefore, the correct option is (D).